THE ROLE OF SMALL BUSINESS IN UZBEKISTAN'S ECONOMIC DEVELOPMENT: CURRENT SITUATION ANALYSIS AND DEVELOPMENT PROSPECTS - A’zamjonova Farangiz Abdubannob qizi; Shokhistakhon Akhunova (Modern American Journals, 2025)
Small business plays a crucial role in fostering sustainable economic growth, increasing employment, and diversifying the economy. In the context of Uzbekistan, the sector has been gaining increasing attention from policymakers and international institutions alike. This study aims to analyze the current state of small business development in Uzbekistan and evaluate its contribution to the national economy. The paper also explores the potential and strategic directions for future growth. The research utilizes a mixed-method approach, incorporating statistical data from national sources (e.g., the State Statistics Committee of Uzbekistan) and analytical reviews of legislative and institutional reforms. Comparative analysis with selected Central Asian countries is also presented. Findings reveal that small businesses account for over 50% of Uzbekistan's GDP and provide employment to a substantial portion of the labour force. However, challenges such as limited access to finance, bureaucratic procedures, and infrastructure gaps persist. Government-led initiatives, including tax incentives, simplified registration processes, and entrepreneurship training programs, are contributing positively to the sector’s growth. To enhance the effectiveness of small businesses as a driver of economic development, Uzbekistan needs to strengthen regulatory frameworks, expand access to financial services, and promote innovation and digitalization. A coherent strategy combining public-private partnerships and regional development programs will be essential in realizing this potential.
Keywords: Small business, Economic development, Uzbekistan, Entrepreneurship, Employment, Private sector, Development strategy, Business environment, Financial access, Institutional reforms.